Prognostic importance of anaemia in patients with acute pulmonary embolism - Donzé, Jacques; Labarère, José; Méan, Marie; Jiménez, David; Aujesky, Drahomir (Thrombosis and Haemostasis, 2011)
Although associated with adverse outcomes in other cardiopulmonary diseases, limited evidence exists on the prognostic value of anaemia in patients with acute pulmonary embolism (PE). We sought to examine the associations between anaemia and mortality and length of hospital stay in patients with PE. We evaluated 14,276 patients with a primary diagnosis of PE from 186 hospitals in Pennsylvania, USA. We used random-intercept logistic regression to assess the association between anaemia at the time of presentation and 30-day mortality and discretetime logistic hazard models to assess the association between anaemia and time to hospital discharge, adjusting for patient (age, gender, race, insurance type, clinical and laboratory variables) and hospital (region, size, teaching status) factors. Anaemia was present in 38.7% of patients at admission. Patients with anaemia had a higher 30-day mortality (13.7% vs. 6.3%; p <0.001) and a longer length of stay (geometric mean, 6.9 vs. 6.6 days; p <0.001) compared to patients without anaemia. In multivariable analyses, anaemia remained associated with an increased odds of death (OR 1.82, 95% CI: 1.60–2.06) and a decreased odds of discharge (OR 0.85, 95% CI: 0.82–0.89). Anaemia is very common in patients presenting with PE and is independently associated with an increased short-term mortality and length of stay.
Keywords: Risk factors; lung; thrombosis